2017
DOI: 10.1294/jes.28.27
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dystocia on blood gas parameters, acid-base balance and serum lactate concentration in heavy draft newborn foals

Abstract: Dystocia is often lethal for neonatal foals; however, its clinicopathological features remain largely unknown. We investigated the effect of dystocia on the foal blood profile. Venous blood samples were collected from 35 foals (5 Percheron and 30 crossbreds between Percheron, Belgian, and Breton heavy draft horses) at 0 hr, 1 hr, 12 hr and 1 day after birth. Dystocia was defined as prolonged labor >30 min with strong fetal traction with or without fetal displacement. The dystocia group (n=13) showed lower mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
3
6
1
Order By: Relevance
“…Overall, our results are in line with previous findings that, even at term, spontaneously delivered foals suffer a degree of hypercapnia and acidosis at birth [26,27,[29][30][31]. A very slight acidemia was present in our SF foals, and consistent with the pH values, the pCO 2 was slightly high, suggesting some respiratory acidosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, our results are in line with previous findings that, even at term, spontaneously delivered foals suffer a degree of hypercapnia and acidosis at birth [26,27,[29][30][31]. A very slight acidemia was present in our SF foals, and consistent with the pH values, the pCO 2 was slightly high, suggesting some respiratory acidosis.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have investigated the blood gas concentrations and acid-base parameters from umbilical vessels immediately after birth in spontaneously delivered and at term induced foals [26][27][28][29]. To the best of our knowledge, only a few papers have reported jugular venous blood gas analyses performed immediately after spontaneous normal and dystocic delivery [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The colostral IgG concentration did not differ between the normal foaling mare and dystocial mare in the present study. Previous studies reported that dystocia causes negative effects on neonatal foals, such as anemia, hypercortisolemia, acidemia, and hyperlacticacidemia [4,10]. It was speculated that dystocia possibly affects the quantity or timing of colostrum intake by the foal and the efficiency of IgG absorption in the intestine and that it results in a decline of foal serum IgG levels.…”
Section: Discussionmentioning
confidence: 99%
“…Dystocia was defined as prolonged labor with strong fetal traction by more than 3 persons or mechanical tools with or without correcting fetal displacement. If stage II (interval between rupture of the chorioallantois until delivery of the foal) was >30 min and labor did not progress, traction was applied to the fetus [10]. Retained fetal membranes was defined as the failure to pass fetal membranes by 3 hr postfoaling [26], and postpartum septic metritis was defined as an elevated rectal temperature of >38.5°C within the first 4 days post-foaling [2].…”
Section: Mare and Foal Conditionsmentioning
confidence: 99%
See 1 more Smart Citation